Prolonged EVLP Using OCS Lung: Cellular and Acellular Perfusates. Issue 10 (October 2017) - Loor, Gabriel; Howard, Brian T.; Spratt, John R.; Mattison, Lars M.; Panoskaltsis-Mortari, Angela; Brown, Roland Z.; Iles, Tinen L.; Meyer, Carolyn M.; Helms, Haylie R.; Price, Andrew; Iaizzo, Paul A.
Abstract : Background: We report the ability to extend lung preservation up to 24 hours (24H) by using autologous whole donor blood circulating within an ex vivo lung perfusion (EVLP) system. This approach facilitates donor lung reconditioning in a model of extended normothermic EVLP. We analyzed comparative responses to cellular and acellular perfusates to identify these benefits. Methods: Twelve pairs of swine lungs were retrieved after cardiac arrest and studied for 24H on the Organ Care System (OCS) Lung EVLP platform. Three groups (n = 4 each) were differentiated by perfusate: (1) isolated red blood cells (RBCs) (current clinical standard for OCS); (2) whole blood (WB); and (3) acellular buffered dextran-albumin solution (analogous to STEEN solution). Results: Only the RBC and WB groups met clinical standards for transplantation at 8 hours; our primary analysis at 24H focused on perfusion with WB versus RBC . The WB perfusate was superior (vs RBC) for maintaining stability of all monitored parameters, including the following mean 24H measures: pulmonary artery pressure (6.8 vs 9.0 mm Hg), reservoir volume replacement (85 vs 1607 mL), and PaO2 :FiO2 ratio (541 vs 223). Acellular perfusion was limited to 6 hours on the OCS system due to prohibitively high vascular resistance, edema, and worsening compliance. Conclusions: The use of an autologous whole donor blood perfusate allowed 24H of preservation without functional deterioration and was superior to both RBC and buffered dextran-albumin solution for extended lung preservation in a swine model using OCS Lung. This finding represents a potentially significant advance in donor lung preservation and reconditioning. Abstract : The authors demonstrate that autologous whole donor blood perfusate results in better outcome compared to RBC and BDAS for 24 hour of lung preservation in a swine model using Organ Care System Lung.